THE INFLUENCE OF HEALTH EDUCATIO THE INFLUENCE OF HEALTH EDUCATION THROUGH AUDIOVISUALS ON THE IMPLEMENTATION OF EXERCISES TO PREVENT STROKE IN THE ELDERLY: THE IMPLEMENTATION OF EXERCISES TO PREVENT STROKE IN THE ELDERLY - Wahyuningsih, Binarti Dwi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
ABSTRACT Stroke attacks the productive age and old age which has the potential to cause new problems in national health development. Preventive measures in the form of pre-hospital treatment need to be emphasized, one way to prevent stroke is by increasing physical activity which is recommended because it is associated with reducing the risk of stroke. but still balance it with adequate rest. This activity can be increased by exercising. The design used in this research is a pre-experimental research design using a One-Group Pre-Post test design. The independent variable in this research is Health Education through AudioVisual. The dependent variable in this research is the implementation of exercise to prevent stroke in the elderly in Randegan village, Driyorejo subdistrict, Gresik regency. Data analysis using the Wilxocon Test was carried out using SPSS 24.0. If r-value > α value (0.05). The results of the research showed that there was an influence before and after being given health education through audiovisual media on the implementation of exercise to prevent stroke, proven by the results of statistical tests using the Wilcoxon test using SPSS, the significance was α=0.05 and the result was r Value = 0.000. The use of audiovisual media in providing health education is very influential, because the media used is easily accepted by the elderly in improving skills, knowledge and changing attitudes related to health. Keywords: Exercise to Prevent Stroke, Health Education, Audiovisual Media, Elderly